Shepherd's Hook: Temporization of Maxillary Removable Partial Denture utilizing an Essix Tray Appliance - Thomas Shepherd, DMD; Mohamed El-Shewy, BDS; William Bachand, DDS (Elsevier, 2024)
Essix trays are commonly used within dentistry for the temporary replacement of missing teeth following extraction of dental alveolar trauma. Typically, this procedure is performed easily with the use of an impression of existing arch, denture tooth, and Essix Tray material. This following report is unique due to the complexity of his existing maxillary dentition being restored with a combination of removable and fixed prosthodontics and the location of the fracture occurring within the esthetic zone. Furthermore, the patient's complex medical history and severe gag reflex added additional factors to the rehabilitation of this patient.A 64-year-old Caucasian male presented to the General Practice Residency with fracture of his fixed partial denture (#9-11). Patient's maxillary arch was restored previously using FPD #6-8 and #9-11 with a Kennedy Class I removable partial denture. Opposing dentition was restored with all ceramic zirconia crowns. Secondary caries noted on fractured #11 deemed non-restorable and #9 fractured equigingival with fair prognosis for restoring via NSRCT, post, core and crown. History of Myocardial Infarction within past year and severe gag reflex. Impressions for this patient required the use of intravenous moderate procedural sedation. Consultation with PCP and cardiologist for medical clearance for moderate sedation were obtained and patient was appointed for impressions, records, and extraction of #9 and #11. Patient was offered plans including traditional denture fabrication, implant retained, or implant fixated prosthesis. Patient requested a temporary prosthesis to allow time to make decision on the final plans due to financial considerations.This case report illustrates a unique application of the Essix Appliance for the temporization of this patient. Additionally, this case report shows a proof of concept for using Essix appliances in temporization of patients already restored with removable prosthesis. The final esthetics, function, and retention of the prosthesis were evaluated as adequate and acceptable to the patient. Pt was able to function with this temporary appliance for 3 months and was restored with an immediate maxillary denture. Patient is being seen for follow up to evaluate patient adaptation to the denture.